Akwinata, Kaliban i Piętaszek na wspólnym bankiecie? Ścieżki i bezdroża antykanibalizmu - Mydla, Jacek (Er(r)go. Teoria - Literatura - Kultura, 2003)
Jacek Mydla Aquinas, Caliban and Friday at a cannibalistic bonfire? The vagaries of the theology of anti-cannibalism. The essay sets out to explore the ideological dispute over cannibalism during the Wars of Religion in its contemporary academic treatment. A special focus of interest is on the theological and metaphysical involvement of the contemporary discourse of cannibalism, represented here by two recent publications: Cannibals by Frank Lestringant (1994) and Cannibalism and The Colonial World (1995), a collection of essays edited by Francis Barker, Peter Hume, and Margaret Iversen. A glance at the recent discourse of cannibalism makes it possible to label it “Protestant" as opposed to “Catholic". References to the religious dispute over transubstantiation, and linguistic reformulations of the theological dilemmas do little justice to the metaphysical traditions on which the Catholic dogma originally rested. The much-discussed imputed allegorisation and symbolisation of the Eucharist corresponds to the allegorisation and symbolisation of the cannibal, characteristic of the colonial experience and its cultural appropriation in the Western world, is itself ridden with ambiguities. revealed in attitudes that scholars display towards religious controversies.